Endogenous noise traders - Marcus Salomonsson (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
We construct a parsimonious model of a financial market where the marginal investor is an endogenous noise trader. Such a trader anticipates that future shocks may force him to exit his position. In compensation he requires a higher return. We show that the original seller of the asset pays the required return. This can only be optimal if the seller has access to an investment opportunity that gives a sufficiently high return, compared to the noise trader's investment opportunities. We also show that, if the noise trader expects to get informative signals, the required return does not necessarily decrease, as claimed in the earlier literature.
Keywords: G14; 330; Market microstructure; no-trade theorems; adverse selection; Finanzmarkt; Kapitalanlage; Noise Trading; Adverse Selection